Case Report Kawasaki Disease - Noventi, Iis; Lukitaningsih, Widya (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Kawasaki disease is a major cause of heart defects that are often found in children. In Indonesia, this disease is still rarely diagnosed because it is still considered rare and not yet widely known. The following two case reports are case reports of boys and girls aged 6 months and 1 year respectively. Both come with persistent fever for more than four days, rashes on the skin, diarrhea, cracked red lips. Patients with the first case got red eyes, peeled skin peeled, swollen neck and swollen legs, reddish tongue but not until like strawberry, the patient was later diagnosed as Kawasaki disease on laboratory examination to get an increase in C-reactive protein, Blood Sedimentation Rate and Thrombocytosis accompanied by a picture echocardiography in case 1 was Dilated A. Right coronary and minimal Pericard effusion. Whereas the second case was accompanied by nausea vomiting, cracked red lips and a strawberry-like tongue, the patient was later diagnosed as Kawasaki disease on laboratory tests to obtain an increase in C-reactive protein, Blood Sedimentation Rate and Thrombocytosis with echocardiographic features of TR Light and mild dilatation RCA . Both children were given intravenous immunoglobulin (IGIV) at a dose of 2 grams / KgBB single dose and aspirin 25 mg 1x1 while in the case of 2 aspilet a dose of 20 mg 1x1.